Pemenuhan Itikad Baik Pelaku Usaha Dalam Memberikan Informasi Kepada Konsumen Layanan Pascabayar - Akhsal Rico Faldy; Hariyo Sulistiyantoro (Jurnal Relasi Publik, 2023)
Every business actor is basically obliged to act in good faith, one of which is as a manifestation of consumer protection. Case in Decision No. 90/Pdt.Sus-BPSK/2021/Pn.Mdn) shows that there are business actors who do not carry out their obligations as they should, namely not having good intentions and not providing information to their consumers. The aim of this research is to explore legal certainty regarding the fulfillment of good faith by business actors in providing information to consumers of postpaid services based on Law of the Republic of Indonesia Number 8 of 1999 concerning Consumer Protection. This research method uses normative juridical approaches to statutory, conceptual and case regulations. The research results found that the fulfillment of good faith in this case showed that legal certainty had not been realized. This is because of the legal provisions regarding this matter as regulated in Law no. 8 of 1999 concerning Consumer Protection has not been enforced properly. According to Sudikno Mertokusumo, legal certainty should be realized by implementing legal provisions as they should.